Theatre & animals - Orozco GarciÌa, Lourdes (Theatre&., 2013)
"All animals have the ability to make us question the human, and its relationship to the other. This cutting-edge text addresses the implications of involving animals in performance. It demonstrates ways in which animals transform theatre's capacity to make meaning, and suggests they expose theatre's negotiations with wider ethical, social and economic questions. Ultimately, the book argues that incorporating animals into performance brings about a reassessment of the ways in which theatre is produced and received." -- Publisher website.